Variable Persister Gene Interactions with (p)ppGpp for Persister Formation in Escherichia coli - Liu, Shuang; Wu, Nan; Zhang, Shanshan; Yuan, Youhua; Zhang, Wenhong; Zhang, Ying (Frontiers in Microbiology, 2017)
Persisters comprise a group of phenotypically heterogeneous metabolically quiescent bacteria with multidrug tolerance and contribute to the recalcitrance of chronic infections. Although recent work has shown that toxin-antitoxin (TA) system HipAB depends on stringent response effector (p)ppGppin persister formation, whether other persister pathways are also dependent on stringent response has not been explored. Here we examined the relationship of (p)ppGpp with 15 common persister genes (dnaK, clpB, rpoS, pspF, tnaA, sucB, ssrA, smpB, recA, umuD, uvrA, hipA, mqsR, relE, dinJ) using E. coli as a model. By comparing the persister levels of wild type with their single gene knockout and double knockout mutants with relA, we divided their interactions into 5 types, namely A “dependent” (dnaK, recA), B “positive reinforcement” (rpoS, pspF, ssrA, recA), C “antagonistic” (clpB, sucB, umuD, uvrA, hipA, mqsR, relE, dinJ), D “epistasis” (clpB, rpoS, tnaA, ssrA, smpB, hipA), and E “irrelevant” (dnaK, clpB, rpoS, tnaA, sucB, smpB, umuD, uvrA, hipA, mqsR, relE, dinJ). We found that the persister gene interactions are intimately dependent on bacterial culture age, cell concentrations (diluted versus undiluted culture), and drug classifications, where the same gene may belong to different groups with varying antibiotics, culture age or cell concentrations. Together, this study represents the first attempt to systematically characterize the intricate relationships among the different mechanisms of persistence and as such provide new insights into the complexity of the persistence phenomenon at the level of persister gene network interactions.